Research progress on the effects and mechanisms of different cell types on osteoclast differentiation in bone metabolism in rheumatoid arthritis - Wei, Yingjun; Xie, Xingwen; Li, Dingpeng; Hou, Xuan; Ren, Ling; Wan, Kangwei (Frontiers in Medicine, 2025)
Rheumatoid arthritis is a systemic autoimmune disease characterized by chronic synovial inflammation, autoantibody production and progressive joint destruction. One of the main pathological features is irreversible damage and dysfunction of bone and joints, and the core pathological link is osteoclast-mediated imbalance of bone metabolism. With the advances in immunology, molecular biology and cytology, different types of cells, including T cells, B cells, macrophages, natural killer cells, synovial fibroblasts and vascular endothelial cells, activate osteoclasts in rheumatoid arthritis, leading to bone metabolism imbalance in RA and causing bone and joint damage. In this paper, we will systematically summarize the effects and mechanisms of different cell types on osteoclast differentiation in rheumatoid arthritis bone metabolism, which will provide theoretical basis and practical guidance for the precise treatment and targeted intervention of RA bone metabolism abnormalities.